Libertad y tricausalidad en la acción: Aquino y Polo. - ENRÍQUEZ, TERESA; VARGAS, ALBERTO I. (Studia Poliana, 2026)
This article examines the notion of the free agent as causa sui in the thought of Thomas Aquinas and Leonardo Polo, analyzing active causal senses –final, efficient, and formal– to determine the scope of tricausality in human action. Leonardo Polo assimilates these causes into elements of cybernetic theory, further situating them within a hierarchy that necessitates transcending causality itself. In Thomas Aquinas, the most profound sense of freedom –love– is understood as servitude according to the final cause. In both authors, love and virtue emerge as the core elements of free causality. In Polo’s work, this is articulated through two distinct neologisms, ‘hyper-formalization’ and ‘hyper-finalization’, the understanding of which requires an examination of freedom beyond the merely causal.